A Floating Island Treatment System for the Removal of Phosphorus from Surface Waters. (October 2018) - Brown, Mark T.; Boyer, Treavor; Sindelar, R.J.; Arden, Sam; Persaud, Amar; Brandt-Williams, Sherry
Abstract: The goal of this project was to design, build, and test a pilot-scale floating modular treatment system for total phosphorus (TP) removal from nutrient-impaired lakes in central Florida, USA. The treatment system consisted of biological and physical–chemical treatment modules. First, investigations of prospective biological and physical–chemical treatment processes in mesocosms and in bench-scale experiments were conducted. Thirteen different mesocosms were constructed with a variety of substrates and combinations of macrophytes and tested for TP and orthophosphate ( PO 4 3 - ) removal efficiencies and potential areal removal rates. Bench-scale jar tests and column tests of seven types of absorptive media in addition to three commercial resins were conducted in order to test absorptive capacity. Once isolated process testing was complete, a floating island treatment system (FITS) was designed and deployed for eight months in a lake in central Florida. Phosphorus removal efficiencies of the mesocosm systems averaged about 40%–50%, providing an average uptake of 5.0 g·m −2 ·a −1 across all mesocosms. The best-performing mesocosms were a submerged aquatic vegetation (SAV) mesocosm and an algae scrubber (AGS), which removed 20 and 50 mg·m −2 ·d −1, respectively, for an average removal of 5.5 and 12.0 g·m −2 ·a −1 for the SAV and AGS systems, respectively. Of the absorptive media, the best performance was alum residual (AR), which reduced PO 4 3 - concentrations by about 75% after 5 min of contact time. Of the commercial resins tested, the PhosX resin was superior to the others, removing about 40% of phosphorus after 30 min and 60% after 60 min. Under baseline operation conditions during deployment, the FITS exhibited mean PO 4 3 - removal efficiencies of 53%; using the 50th and 90th percentile of PO 4 3 - removal during deployment, and the footprint of the FITS system, yielded efficiencies for the combined FITS system of 56% and 86%, respectively, and areal phosphorus removal rates between 8.9 and 16.5 g·m −2 ·a −1 .